THE RELATIONSHIP BETWEEN THE APPLICATION OF THERAPEUTIC COMMUNICATION AND THE QUALITY OF NURSING SERVICES AT THE PRATAMA RESTU PIRNAWAT CLINIC, WAY PANJI LAMPUNG SELATAN DISTRICT IN 2022 - Christyana, Valencia Clara; Simamora, Rotua Suriany; Agustina, Lisna (Soscience: Jurnal Ilmu Sosial Science, 2023)
Nursing communication is the basis and key for a nurse in carrying out nursing care. Communication carried out by nurses serves to listen to patient complaints and can explain the planned nursing action procedures. Nurses are required to be able to communicate well with patients. If it is not applied, it will interfere with the therapeutic relationship which will have an impact on the quality of nurse service quality. Research objective to find out the relationship between the application of therapeutic communication with the quality of nurse services at the Pratama Restu Pirnawat Clinic, Way Panji Lampung Selatan District in 2022. Research the method used by researchers is quantitative. The design in this study used observational analytic using a cross sectional approach. Research result It was found that the p-value is (0.00) < (0.05). This shows that Ho is rejected and Ha is accepted. Based on the results of the study, there is a significant relationship between the application of therapeutic communication with the quality of nurse services at the Pratama Restu Pirnawat Clinic, Way Panji Lampuung Selatan District in 2022.